Induksi Embriogenesis Somatik dari Jaringan Endosperma Jeruk Siam (Citrus nobilis Lour.) cv Simadu - Kosmiatin, Mia; Purwito, Agus; Wattimena, Gustaff Adolf; Mariska, Ika (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTTriploid plants can be obtained from endosperm tissues through somatic embryogenesis regeneration. This research aimed to obtain somatic embryogenesis regeneration technique of tangerine endosperm. There were 3 experiments conducted in this research: 1) Embryogenic callus induction of tangerine endosperm. Endosperms isolated from fruits that were harvested from mother plants 11-13 weeks after anthesis and cultured on Murashige and Skoog (MS) medium by modified vitamin Morel and Wetmore (MW) which treated by 0.1 mg L-1 biotin, 500 mg L-1 malt extract (ME), 500 mg L-1 Casein hydrolisate (CH), 500 mg L-1 ME + 0.1 mg L-1 biotin, and 500 mg L-1CH + 0.1 mg L-1 biotin, 2) Maturation and germination of somatic embryos conducted by embryogenic callus cultured on MS medium by vitamin MW modified with addition of ABA, glutamine, and biotin, and 3) Plantlet elongation conducted on MS medium modified by MW vitamin with addition of GA3 and Kinetin. The best induction medium for embryogenic callus was modified MS enriched with 3 mg L-1 BA and 500 L-1 CH or ME, in succession 84.0 and 80.0%. The best medium for somatic embryos maturation with normal morphological plantlets (54.8%) was modified MS medium without plant growth regulator with higher rate of solidified agent (from 2.5 to 3 g L-1 Phytagel). Plantlets elongation was highly (0.9 cm) occurred on modified MS with enriched of 2.5 mg L-1 GA3. Keywords: Citrus nobilis (Lour.), endosperm culture, in vitro, Simadu tangerine